The Effect of Hiv/Aids Scourge on Food Security in Nyabbani Sub-County, Kitagwenda District. - Ainembabazi, Docus (Kabale University, 2023)
The researcher intended to find out the effect of the HIV/AIDS scourge on food security in the Nyabbani sub-county, Kitagwenda district.